I Like My Family! - Hanson, Anders 1980- (Edina, Minn : ABDO Pub. Co., 2006)
Using rebuses and simple sentences, introduces the things that different members of a family like.
"SandCastle."
"SandCastle level--beginning"--T.p. verso.
Keywords: Vocabulary; Rebuses